Novel compact design high gain DC–DC step up converter applicable for PV applications. (June 2022) - Purushothaman, S.K.; Sattianadan, D.; Vijayakumar, K.
Abstract: In Today's world modern requirement of the need of natural given renewable energy sources such as solar photovoltaics, wind energy and fuel cells can beeasily integrated for DC micro gridapplications and PV type model applications. It is highly required to obtain more efficient dc-dc converters for the usage of micro grid and EV applications. The traditional converters lack in efficiency and the volume is complicated to handle. Here we have designed a new converter by not adding any additional booster components like VMC or super capacitors. The new topology uses only one inductor to improve the output voltage during discharging/charging mode. The duty ratios technique used will minimizing the switching losses. Comparatively, with less number of components the high voltagegain obtained in this dc-dc converter. The output and the efficiency of our newer design is achieved by using different duty ratios. A converter design circuit is developed with input and output voltage ratio of 20/270 V. and their performance analysis is discussed by output results.